Analisis Keterampilan Teknik Dasar Bola Basket Pada Mahasiswa - Rifky Mile; Irawan, Safri; Agung Prasetyo; Meri Haryani; I Kadek Suardika; Arief Ibnu Haryanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the level of basic basketball technical skills of student athletes in the Sports Coaching Education Study Program at Gorontalo State University, including dribbling, passing, and shooting. This study used a quantitative approach with a descriptive survey design. The research subjects were 30 male student athletes selected using a purposive sampling technique based on the criteria of active training and competition experience. The research instrument was a basic basketball technical skills test consisting of zigzag dribbling, passing to the target, and shooting (free throw and set shoot). Data were analyzed using descriptive statistics including mean values, standard deviations, and percentages to determine ability categories. The results showed that passing skills were in the good category, while dribbling and shooting were in the adequate category. Overall, the basic technical skills of student athletes were still uneven, with passing being the most dominant skill and shooting being the lowest aspect. These findings indicate the need to strengthen basic technical training programs that are more balanced between individual skills and team skills to improve student athletes' performance in basketball games at the college level.